Unbalanced Metalloproteinase-9 and Tissue Inhibitors of Metalloproteinases Ratios Predict Hemorrhagic Transformation of Lesion in Ischemic Stroke Patients Treated with Thrombolysis: Results from the MAGIC Study - Piccardi, Benedetta; Palumbo, Vanessa; Nesi, Mascia; Nencini, Patrizia; Gori, Anna Maria; Giusti, Betti; Pracucci, Giovanni; Tonelli, Paolina; Innocenti, Eleonora; Sereni, Alice; Sticchi, Elena; Toni, Danilo; et al. (Frontiers in Neurology, 2015)
Background Experimentally, metalloproteinases (MMPs) play a detrimental role related to severity of ischemic brain lesions. Both MMPs activity and function in tissues reflect the balance between MMPs and tissue inhibitors of metalloproteinases (TIMPs). We aimed to evaluate the role of MMPs/TIMPs balance in the setting of rtPA treated stroke patients Methods Blood was taken before and 24-hours after rtPA from 327 patients (mean age 68 years, median NIHSS 11) with acute ischemic stroke. Delta median values of each MMP/TIMP ratio [(post rtPA MMP/TIMP-baseline MMP/TIMP)/(baseline MMP/TIMP)] were analyzed related to symptomatic intracranial hemorrhage (sICH) according to NINDS criteria, relevant hemorrhagic transformation (HT) defined as hemorrhagic infarction type 2 or any parenchimal hemorrhage, stroke subtypes (according to Oxfordshire Community Stroke Project) and 3-month death. The net effect of each MMP/TIMP ratio was estimated by a logistic regression model including major clinical determinants of outcomes Results Adjusting for major clinical determinants, only increase in MMP9/TIMP1 and MMP9/TIMP2 ratios remained significantly associated with sICH (odds ratio [95% confidence interval], 1.67 [1.17 – 2.38], p = 0.005; 1.74 [1.21 – 2.49], p=0.003 respectively). Only relative increase in MMP9/TIMP1 ratio proved significantly associated with relevant HT (odds ratio [95% confidence interval], 1.74 [1.17 – 2.57], p=0.006) with a trend towards significance for MMP9/TIMP2 ratio (p=0.007). Discussion Our data add substantial clinical evidence about the role of MMPs/TIMPs balance in rtPA treated stroke patients. These results may serve to generate hypotheses on MMPs inhibitors to be administered together with rtPA in order to counteract its deleterious effect.